Analisis Perilaku Kurs IDR/USD Berdasarkan Model Hooper-Morton (Analyze The Behavior of Exchange Rate IDR/USD Based on Hooper-Morton’s Model) - Alvin Sugeng Prasetyo (MediaTrend, 2018)
This study aims to analyze the behavior of the rupiah/US$ based on the Hooper-Morton model approach. The method used is ECM with time series data of 2002 quarter 1 to 2017 quarter 4 in Indonesia. The conclusion of this study is the difference of M2 growth, the difference of economic growth, the difference of inflation, and the difference of growth of trade balance have significant influence to rupiah/US$ in long term and short term.